A Study of the Influence of Interior on Comfort in Outpatient Unit Waiting Room at Hospitals in Lhokseumawe - Effan Fahrizal; Muhammad Imam; Soraya Masthura Hassan; Eri Saputra (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Important role in the comfort of patients. Based on field observation, patients and visitors felt uncomfortable and bored while waiting in the queue to consult a doctor. Hospital visitors are not all ill patients but there are also those who only consult, escort, or visit. In this case, the beauty and comfort in the waiting area, which is a public and intermediary area, is expected to have a psychological effect that can distract visitors from a terrifying impression, provide comfortability while waiting and reduce patient tension before being examined. This study examines the influence of interior on the comfort of patients in the waiting room with case studies at Abby Hospital, Bunda Women and Children Hospital, and PMI Hospital. This study uses a qualitative method with a correlation method approach. Research variables include (1) circulation, (2) cleanliness, (3) noise, (4) lighting, (5) beauty, (6) aromas/odors. The findings show that at Bunda Women and Children Hospital, 32% of the respondents felt uncomfortable with the layout of the room (facilities/furniture), 64% of respondents felt comfortable, 4% of respondents felt very comfortable. While at PMI Hospital, 36% of respondents felt uncomfortable with the layout of the room (facilities/furniture), 56% of respondents felt comfortable, 4% of respondents felt very comfortable. Finally, at Abby Hospital, 0% of respondents felt uncomfortable with the layout of the room (facilities/furniture), 68% of respondents felt comfortable, 32% of respondents felt very comfortable. In this study, conclusions were drawn for basic guidelines for hospital comfort in terms of advantages and disadvantages.